Sustained Antibody-Dependent NK Cell Functions in Mild COVID-19 Outpatients During Convalescence - Fuentes-Villalobos, Francisco; Garrido, Jose L.; Medina, Matías A.; Zambrano, Nicole; Ross, Natalia; Bravo, Felipe; Gaete-Argel, Aracelly; Oyarzún-Arrau, Aarón; Amanat, Fatima; Soto-Rifo, Ricardo; Valiente-Echeverría, Fernando; Ocampo, Renato; et al. (Frontiers in Immunology, 2022)
The current coronavirus disease 2019 (COVID19) pandemic has left researchers scrambling to identify the humoral immune correlates of protection from COVID-19. To date, the antibody mediated correlates of virus neutralization have been extensively studied. However, the extent that non-neutralizing functions contribute to anti-viral responses are ill defined. Therefore, in this study, we profiled the anti-spike antibody subtype/subclass responses, along with neutralization and antibody-dependent natural killer cell functions in 83 blood samples collected between 4 and 201 days post-symptoms onset from a cohort of COVID-19 outpatients. We observed heterogeneous humoral responses against the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spike protein. Overall, anti-spike profiles were characterized by a rapid rise of IgA and sustained IgG titers. In addition, strong antibody-mediated natural killer effector responses correlated with milder disease and being female. While higher neutralization profiles were observed in males along with increased severity. These results give an insight into the underlying function of antibodies that can extend beyond their ability to block infection via neutralization and suggest that antibody-mediated natural killer cell activity is a key function of the humoral response against the SARS-CoV-2 spike protein.